Intergenerational mobility in Latin America: the multiple facets of social status and the role of mothers - Ciaschi, Matías Omar (2021)
Typical intergenerational mobility studies focus on a single measure of an underlying latent social status; this procedure can lead to attenuation biases in intergenerational persistence estimates. This paper aims to extend the model to integrate different proxy measures in one unified framework for Latin American countries. Following the Lubotsky and Wittenberg (2006) approach, we: i) provide a more comprehensive study of intergenerational mobility considering not only the education but also the occupation of both parents as proxies for family background; ii) compare the relevance of each single proxy in explaining the evolution of intergenerational mobility, particularly the importance of mother’s characteristics. Our findings suggest that intergenerational persistence estimates are between 26% and 40% higher when considering parents’ occupation (and not only education) as proxies for family background. Additionally, mother’s attributes have been increasing their relative importance in family background throughout the years; particularly, mother’s characteristics became at least equally important than fathers’ ones since the 1980s.